Trends and drivers of the development of local consumer services markets - A. A. Eliseeva; E. B. Dvoryadkina (Модернизация, инновация, развитие, 2023)
Purpose: is to develop a methodological approach to determining trends and drivers of the development of local consumer services markets.Methods: this study is based on a systematic methodological approach that allows identifying local consumer services markets as components of the regional consumer market in general, and the regional services market in particular. The research is also based on the application of general scientific methods of analysis, synthesis, comparison, as well as on the application of methods of economic and statistical analysis of dynamics and groupings, analytical data processing, analogies, scientific generalizations. Considering that the object of the study is the markets of household services localized within municipalities, spatial analysis methods were used in the study.Results: the methodology of analysis of the local market of household services has been developed, including the following stages: 1) determination of the object of research; 2) analysis and evaluation of indicators of the development of local markets of household services (volumes of household services to the population of municipalities; the scale of the presence of municipalities in the economy of the region in terms of the volume of paid services to the population; the provision of the population of municipalities with objects and points of consumer services; the structure of the markets of household services by type of services; availability of human resources for the sphere of consumer services of municipalities); 3) interpretation of the results. The methodology was tested on the example of municipalities of the Sverdlovsk region – leaders in terms of paid services to the population.Conclusions and Relevance: trends in the development of local consumer services markets have been identified. The most important of them are the preservation of stability and heterogeneity of the specific structure of local consumer services markets, a moderate pace of commissioning of consumer services facilities, insignificant dynamics of indices of the physical volume of household services to the population, the collapse of consumer services markets due to the impact of the COVID–19 pandemic. The problems of the development of local consumer services markets are revealed, and these are imperfection of the legal regulation of consumer services, lack of qualified personnel, insufficient financial resources to increase the level of provision of the population with consumer services, low level of development of mobile forms of provision of household services, etc. The drivers of the development of local consumer services markets have been identified.